1984
DOI: 10.2136/sssaj1984.03615995004800040045x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Effects of Manganese (IV), Iron(III), Aluminum, and Silicon Oxides on the Formation of Phenolic Polymers

Abstract: The catalytic effects of three Mn(IV) oxides (birnessite, cryptomelane, and pyrolusite) and short‐range ordered Fe(III), Al, and Si oxides on the darkening of phenolic compound solutions (hydroquinone, resorcinol, and catechol) and the subsequent formation of humic acid (the precipitate formed by acidifying the darkening solution) were investigated. Manganese oxides are very powerful in causing the darkening of phenolic compounds. The rate and degree of the darkening vary with the kinds of Mn oxides, the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(84 citation statements)
references
References 0 publications
6
78
0
Order By: Relevance
“…Changes in the IR spectra of P sorbed on Fe gel took place when the amount of hydroquinone was 960/.tmol or higher, which is more than 30 times the lower limit for ascorbic acid. A similar difference in the reactivity among position isomers of polyphenols was also observed in the oxidative reaction of the polyphenols in the presence of hydrous Fe oxide and Mn oxides (Shindo and Huang 1984;McBride 1989).…”
Section: Resukts and Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Changes in the IR spectra of P sorbed on Fe gel took place when the amount of hydroquinone was 960/.tmol or higher, which is more than 30 times the lower limit for ascorbic acid. A similar difference in the reactivity among position isomers of polyphenols was also observed in the oxidative reaction of the polyphenols in the presence of hydrous Fe oxide and Mn oxides (Shindo and Huang 1984;McBride 1989).…”
Section: Resukts and Discussionsupporting
confidence: 69%
“…Diphenols such as hydroquinone, resorcinol, and catechol were oxidatively darkened by the presence of hydrous Fe oxide though the degree of darkening was much less pronounced than that by Mn oxides (Shindo and Huang 1984). Okazaki et al (1976) suggested that polyphenols are one of the materials responsible for the dissolution of Mn in a paddy soil under reducing conditions.…”
mentioning
confidence: 99%
“…As such, the data indicate that the diagenetic progresses were slower in Milli-Q water and that the polymerization of tannins seems to be the dominant process. The difference in the reactivity of tannins in natural waters may thus result from differences in pH, trace-metal concentrations (especially transition metals; Shindo and Huang 1984), and coexisting DOM quality and quantity (Sandvik et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, birnessite, kaolin and nontronite have been reported to enhance the formation of dark-colored polymer from amino acids and quinones [4][5][6][7][8][9]. In addition, oxides of Si, Mn, Al and Fe have also been reported to facilitate the darkening of reaction mixtures that contain humic precursors [10,11].…”
Section: Introductionmentioning
confidence: 99%